A day in the life of a psychiatrist in 2050: where will the algorithm take us?. (June 2020) - Gillett, George
Summary: Digital phenotyping (such as using live data from personal digital devices on sleep, activity and social media interactions) to monitor and interpret people's current mental state is a newly emerging development in psychiatry. This article offers an imaginary insight into its future potential for both psychiatrist and patient.